Sensitive Detection of Trace Explosives by a Self-Assembled Monolayer Sensor - Weitao Liu; Wajid Ali; Ye Liu; Mingliang Li; Ziwei Li (Micromachines, 2023)
Fluorescence probe technology holds great promise in the application of trace explosive detection due to its high sensitivity, fast response speed, good selectivity, and low cost. In this work, a designed approach has been employed to prepare the TPE-PA-8 molecule, utilizing the classic aggregation-induced emission (AIE) property of 1,1,2,2-tetraphenylethene (TPE), for the development of self-assembled monolayers (SAMs) targeting the detection of trace nitroaromatic compound (NAC) explosives. The phosphoric acid acts as an anchoring unit, connecting to TPE through an alkyl chain of eight molecules, which has been found to play a crucial role in promoting the aggregation of TPE luminogens, leading to the enhanced light-emission property and sensing performance of SAMs. The SAMs assembled on Al2O3-deposited fiber film exhibit remarkable detection performances, with detection limits of 0.68 ppm, 1.68 ppm, and 2.5 ppm for trinitrotoluene, dinitrotoluene, and nitrobenzene, respectively. This work provides a candidate for the design and fabrication of flexible sensors possessing the high-performance and user-friendly detection of trace NACs.